Solid magnesium ion electrolyte based on pyridine ligand and preparation method and application thereof

By introducing pyridine ligands into MgB12H12 hydrate to replace water molecules and form a Mg(C5H5N)x2+ and [B12H12]2- complex, the passivation layer problem of MgB12H12 hydrate electrolyte material was solved, achieving high conductivity and stable magnesium ion conduction, thus improving electrochemical performance and the feasibility of preparation.

CN121471130APending Publication Date: 2026-02-06CHONGQING UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511591985.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-03
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing MgB12H12 hydrate electrolyte materials form a passivation layer on the magnesium anode, which prevents magnesium ion dissolution/deposition reactions, resulting in decreased electrochemical performance and insufficient conductivity.

Method used

By introducing pyridine ligands to replace water molecules in MgB12H12 hydrate, a Mg(C5H5N)x2+ and [B12H12]2- anionic complex is formed. The Lewis basicity of pyridine is stronger than that of water in its coordination ability, which stabilizes the electrode-electrolyte interface and enables reversible magnesium ion conduction.

Benefits of technology

It significantly improves the conductivity of magnesium ion electrolytes, avoids the formation of passivation layers, enhances electrochemical performance, and has a simple preparation process, low cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121471130A_ABST
    Figure CN121471130A_ABST
Patent Text Reader

Abstract

The invention discloses a solid magnesium ion electrolyte based on a pyridine ligand, which is a compound composed of Mg (C5H5N) x < 2 + > composite cations and [B12H12] 2-anions, and x is greater than or equal to 1 and less than or equal to 6; the number of the pyridine ligands is 6. The preparation method comprises the following steps: step 1, preparing a Mg (H2O) 3B12H12 precursor MBH-W; and step 2, preparation of Mg (C5H5N) 6B12H12MBH-P. The preparation method comprises the following steps: preparing Mg (C5H5N) When the MBH-P-100 is applied as a magnesium ion solid electrolyte, the conductivity of the MBH-P-100 is 10 <-4 > S cm <-1 > under the condition that the working temperature is 140 DEG C; under the conditions that the polarization voltage is 1V, the test time is 4000 seconds and the test temperature interval is 120 DEG C, the electronic conductivity is 10 <-8 > S cm <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of energy storage materials, and particularly relates to a solid-state magnesium ion electrolyte based on a pyridine ligand and a preparation method and application thereof. BACKGROUND

[0002] The rechargeable magnesium battery has the advantages of high energy density up to 3832 mAh cm -2 and rich magnesium resource reserves, but the electrode material has the problems of low oxidation stability, high corrosion, and nucleophilicity, and the existing rechargeable magnesium battery electrolyte has the problems of volatility and flammability, so that the rechargeable magnesium battery based on the liquid electrolyte cannot meet the application requirements. The solid-state electrolyte has the characteristics of not containing organic solvents, and solves the problems of easy leakage, volatility, and flammability of the liquid electrolyte. In addition, the rechargeable magnesium battery based on the solid-state electrolyte also has the advantages of high energy density, wide temperature adaptability, and inhibition of dendrite growth. In the solid-state electrolyte material, the magnesium borohydride-based complex hydride has the advantages of stability to the magnesium negative electrode and high magnesium ion mobility in addition to the characteristics of non-volatility and non-flammability of the conventional solid-state electrolyte, high mechanical strength, and good flexibility. However, the magnesium borohydride-based complex hydride represented by Mg(BH4)2 has the problem that the electrical conductivity is only 10 -13 S cm -1 when the working temperature is 100℃.

[0003] In order to improve the electrical conductivity of Mg(BH4)2, neutral ligands such as NH3 or NH2(CH2)2NH2 can be introduced to increase the Mg-B bond distance, thereby reducing the magnesium ion migration energy barrier, achieving the effect of improving the magnesium ion migration rate, and ultimately achieving the effect of improving the electrical conductivity performance of the Mg(BH4)2-based solid-state electrolyte. For example, the existing document 1 (S. Higashi, K. Miwa, M. Aoki, K. Takechi, et al. A novel inorganic solid state ion conductor for rechargeable Mg batteries [J]. Chemical Communications, 2014, 50: 1320-1322.) proves by experiments that the Mg ion conductivity of Mg(BH4)(NH2) can reach 10 -6 S cm -1 when the working temperature is 150℃. The reason is that the introduction of (NH2) - ion ligand improves the conduction of magnesium ions. However, in Mg(BH4)2, the anion BH4 -It has poor thermodynamic stability, which makes it prone to local electron delocalization, leading to a technical problem of decreased electrochemical performance.

[0004] To address the poor thermodynamic stability of Mg(BH4)2, [B] can be selected. 10 H 10 ] 2- and [B] 12 H 12 ] 2- As an anion, the reason is that [B 10 H 10 ] 2- Or [B] 12 H 12 ] 2- Anions possess greater symmetry, thus exhibiting a stronger paddlewheel effect, which can enhance ion migration rates. For example, existing literature 2 (K. Kisu, A. Dorai, S. Kim, et al. "Fast divalent conduction in MB") 12 H 12 .12H2O(M=Zn,Mg)complex hydrides:effects of rapidcrystal water exchange and application for solid-state electrolytes》[J].Journal of Materials Chemistry A, 2022,10:24877-24887.) MgB was prepared 12 H 12 The .12H2O solid electrolyte material exhibits a magnesium ion conductivity of 6.1 × 10⁻⁶ at an operating temperature of 50°C. -5 S cm -1 The reason why this technical solution significantly improves ionic conductivity is that MgB 12 H 12 Rapid exchange of water of crystallization in .12H2O and [B 12 H 12 ] 2- The anion's propeller effect enhances the migration of magnesium ions. However, according to the test results in existing literature 2, MgB... 12 H 12 As a battery containing an electrolyte material, magnesium ion migration cannot be detected during charge-discharge cycles, meaning it does not function as a solid magnesium ion electrolyte.

[0005] This leads to the above regarding MgB 12 H 12The technical problems with the base electrolyte material can be explained by existing literature 3 (J. Zhang, J. Liu, M. Wang, et al. "The origin of anode-electrolyte interfacialpassivation in rechargeable Mg-metal batteries" [J]. Energy & Environmental Science, 2023, 16: 1111-1124.). Specifically, the reason is that the Mg anode and Mg(H2O)6B... 12 H 12 The water molecules in the .6H2O electrolyte react to form a passivation layer, which prevents the subsequent dissolution / deposition of magnesium ions, ultimately resulting in the lack of electrochemical performance. Summary of the Invention

[0006] The purpose of this invention is to provide a solid magnesium ion electrolyte based on pyridine ligands, its preparation method, and its applications. This addresses the aforementioned issues related to MgB... 12 H 12 The passivation layer problem caused by hydrates can be addressed by reconstructing a stable electrode-electrolyte interface, thereby breaking down the passivation layer and enabling reversible deposition / dissolution of the magnesium metal anode. Specifically, this involves eliminating any substances in the electrolyte that would cause anode passivation, specifically MgB2. 12 H 12 The coordinated water in the hydrate, based on this, also needs to be accounted for [B]. 12 H 12 ] 2- Anions can reversibly and rapidly conduct magnesium ions within the bulk phase.

[0007] Based on the above fundamental principles, the specific technique employed in this invention is to introduce an excess of pyridine solution. By utilizing the stronger Lewis basicity and coordination ability of the nitrogen atom in the pyridine molecule (C5H5N) compared to the oxygen atom in the water molecule, the pyridine molecule can achieve the desired effect on Mg(H2O)3B. 12 H 12 The water molecules in the intermediate coordination undergo displacement, that is, they compete with and replace Mg through pyridine. 2+ The three H2O molecules that coordinate directly eventually form the cationic species Mg(C6H6N) with pyridine as the ligand. x 2+ Where 1≤x≤6; excess pyridine serves as both a ligand and a solvent in the technical solution, utilizing the high-concentration ligand environment to shift the ligand exchange equilibrium toward the formation of a more stable complex, ultimately yielding Mg(C5H5N). x B 12 H 12 .

[0008] To achieve the above-mentioned objectives, the technical solution adopted by this invention is as follows:

[0009] A solid magnesium ion electrolyte based on pyridine ligands, consisting of Mg(C6H6N). x 2+ Complex cations and [B] 12 H 12 ] 2- Compounds composed of anions, wherein 1 ≤ x ≤ 6; the number of pyridine ligands is 6.

[0010] A method for preparing a solid magnesium ion electrolyte based on pyridine ligands includes the following steps:

[0011] Step 1, Mg(H2O)3B 12 H 12 The preparation of the precursor first involves Li2B 12 H 12 Dissolved in deionized water, solution A is obtained. Then, under certain conditions, a strong acid ion exchange resin is added to solution A and magnetically stirred to obtain solution B. Excess MgCO3 is added to solution B to react and obtain the precursor solution. Finally, the precursor solution is washed, filtered, and dried to obtain the precursor Mg(H2O)3B. 12 H 12 Abbreviated as MHB-W;

[0012] In step 1, Li2B 12 H 12 The mass ratio of hydride to MgCO3 is 3:1;

[0013] In step 1, the conditions for stirring solution B are: stirring temperature of 20-40℃ and stirring time of 8-12h.

[0014] In step 1, the precursor solution is dried by rotary evaporation of the filtrate obtained from filtration to obtain Mg(H2O)6B. 12 H 12 Mg(H2O)6B crystals were then dried at 150℃ for 12-18 hours. 12 H 12 .6H2O crystals were vacuum dried;

[0015] Step 2, Mg(C5H5N)6B 12 H 12To prepare the solution, firstly, under argon atmosphere, the MBH-W obtained in step 1 is placed in a pyridine solution and heated and stirred under certain conditions to obtain a homogeneous mixed liquid. Then, the mixed liquid is vacuum dried to obtain the solid magnesium ion electrolyte Mg(C5H5N)6B based on pyridine ligands. 12 H 12 Abbreviated as MBH-P;

[0016] In step 2, the mass ratio of MBH-W to pyridine solution is 1:100;

[0017] In step 2, the heating and stirring conditions are as follows: heating temperature is 30-50℃, and stirring time is 20-30h.

[0018] In step 2, the vacuum drying conditions are: drying temperature of 100℃ and drying time of 3-8 hours.

[0019] When used as a solid magnesium ion electrolyte based on pyridine ligands, MBH-P-100 exhibits a conductivity of 10⁻⁶ at an operating temperature of 140°C. -4 S cm -1 Under the conditions of a polarization voltage of 1V, a test time of 4000s, and a test temperature range of 120℃, the electronic conductivity is 10. -8 S cm -1 .

[0020] The technical effects of this invention have been tested experimentally, and the specific results are as follows:

[0021] XRD and FTIR tests show that the method of this invention successfully removes water molecules from the electrolyte, introduces pyridine ligands, and achieves complete conversion of MBH-W to MBH-P.

[0022] TG and weighing tests showed that MBH-P contained 6 pyridine ligands and had an initial weight loss temperature of 110℃. Therefore, combined with subsequent conductivity tests, it can be demonstrated that drying temperature has a substantial impact on the chemical composition of MBH-P, and thus significantly affects its conductivity performance.

[0023] Conductivity tests show that MBH-P maintains a conductivity of 10⁻⁶ even at an operating temperature of 140℃. -4 S cm -1 The improvement is three orders of magnitude, and the conductivity can still reach 5.3 × 10⁻⁶ under the condition of operating temperature of 90℃. -6 S cm -1 It is still significantly higher than MBH-W or MBH-P-Na;

[0024] Meanwhile, electron mobility number testing revealed that the steady-state current of the MBH-P reaches the milliampere level, corresponding to an electronic conductivity as low as 10. -8 S cm -1 It has excellent ion conductivity.

[0025] Therefore, the present invention has the following advantages over the prior art:

[0026] 1. Mg(C5H5N)6B 12 H 12 As a solid magnesium ion electrolyte, it can avoid side reactions with the magnesium anode to form a passivation layer and improve the electrochemical performance of the electrolyte;

[0027] 2. Mg(C5H5N)6B 12 H 12 As a solid magnesium ion electrolyte, it has high ionic conductivity.

[0028] 3. Mg(C5H5N)6B 12 H 12 It has the advantages of low cost, simple preparation process, controllable reaction and easy large-scale preparation. Attached Figure Description

[0029] Figure 1 This is the XRD pattern of the MHB-W obtained in Embodiment 1 of the present invention;

[0030] Figure 2 This is the FTIR image of the MHB-W obtained in Embodiment 1 of the present invention;

[0031] Figure 3 This is the temperature-conductivity diagram of MBH-W obtained in Embodiment 1 of the present invention;

[0032] Figure 4 This is the XRD pattern of MBH-P-100 obtained in Embodiment 1 of the present invention;

[0033] Figure 5 This is the FTIR image of MBH-P-100 obtained in Embodiment 1 of the present invention;

[0034] Figure 6 This is the TGA diagram of MBH-P-100 obtained in Embodiment 1 of the present invention;

[0035] Figure 7 This is the temperature-conductivity diagram of MBH-P-100 obtained in Example 1 of the present invention;

[0036] Figure 8 This is the electron mobility graph of MBH-P-100 obtained in Embodiment 1 of the present invention;

[0037] Figure 9This is a cyclic charge-discharge diagram of the MBH-P-100 obtained in Embodiment 1 of the present invention;

[0038] Figure 10 This is a cyclic charge-discharge diagram of MBH-P-150 obtained in Comparative Example 1 of this invention;

[0039] Figure 11 This is the temperature-conductivity diagram of MBH-P-170 obtained in Comparative Example 2 of this invention;

[0040] Figure 12 This is the temperature-conductivity diagram of MBH-P-Na obtained in Comparative Example 3 of this invention. Detailed Implementation

[0041] The present invention will be further described in detail through embodiments and with reference to the accompanying drawings, but this is not intended to limit the scope of the invention.

[0042] Example 1

[0043] A method for preparing a solid magnesium ion electrolyte based on pyridine ligands includes the following steps:

[0044] Step 1, Mg(H2O)3B 12 H 12 To prepare the precursor, firstly, 1g of Li2B... 12 H 12 Dissolved in 160 mL of deionized water to obtain solution A, then, with stirring at 30 °C for 10 h, 30 mL of strong acid ion exchange resin was added to solution A and magnetically stirred to obtain solution B. Next, with stirring at 30 °C for 1 h, 0.45 g (excess MgCO3) was added to solution B to react and obtain the precursor solution. Finally, the precursor solution was washed, filtered, and dried to obtain precursor Mg(H2O)3B. 12 H 12 Abbreviated as MHB-W;

[0045] In step 1, the precursor solution is dried by rotary evaporation of the filtrate obtained from filtration to obtain Mg(H2O)6B. 12 H 12 Mg(H2O)6B crystals were then dried at 150°C for 15 hours. 12 H 12 MBH-W can be obtained by vacuum drying of .6H2O crystals;

[0046] To confirm the composition of MBH-W, XRD tests were performed. The test results are as follows: Figure 1 As shown, MBH-W contains Mg(H2O)3B. 12 H12 The characteristic peaks were observed. Test results indicate that step 1 successfully prepared the MBH-W precursor.

[0047] To further confirm the composition of MBH-W, FTIR testing was performed. The test results are as follows: Figure 2 As shown, MBH-W has B 12 H 12 2- Boron cage structure and OH bonds.

[0048] To demonstrate the conductivity performance of MBH-W, an AC impedance test was performed on the MBH-W obtained in step 1. The specific method for the AC impedance test was as follows: first, a tableting pressure of 100 MPa cm⁻¹ was applied. -2 The sample to be tested is pressed into an electrolyte sheet with a diameter of 10 mm. Then, using the electrolyte sheet as a solid electrolyte and a molybdenum sheet as an electrode, a battery is assembled. The resulting battery is referred to as MBH-W. The AC voltage is 10 mV, and the frequency is 0.01-10. 6 The conductivity performance of MBH-W was tested at Hz under conditions ranging from 30 to 140°C. The test results are shown in Table 1 and... Figure 3 As shown, at an operating temperature of 140℃, the conductivity of MBH-W is 7.7 × 10⁻⁶. -8 S cm -1 .

[0049] Table 1 MHB-W Temperature-Conductivity Values

[0050]

[0051] Step 2, Mg(C5H5N)6B 12 H 12 To prepare the solution, firstly, under argon atmosphere, 0.65 g of MBH-W obtained in step 1 was placed in 70 mL of pyridine solution and heated and stirred at 40 °C for 24 h to obtain a homogeneous mixed liquid. Then, the mixed liquid was vacuum dried at 100 °C for 5 h to obtain the solid magnesium ion electrolyte Mg(C5H5N)6B based on pyridine ligands. 12 H 12 It is abbreviated as MBH-P; since the drying temperature of MBH-P obtained in Example 1 is 100℃, the specific Example 1 is named MBH-P-100.

[0052] To verify the composition of MBH-P-100, XRD tests were performed. The test results are as follows: Figure 4As shown, the diffraction peaks of MBH-P-100 are located differently from those of MBH-W. The test results indicate that introducing a pyridine ligand in step 2 converts MBH-W into MBH-P-100.

[0053] To further confirm the composition of MBH-P-100, FTIR testing was performed. The test results are as follows: Figure 5 As shown, MBH-P-100, in addition to having B 12 H 12 2- The boron cage structure still contains CH and CC bonds, while the OH bonds are absent. Test results show that step 2 transforms MBH-W into MBH-P-100.

[0054] To further confirm the number of pyridine ligands in MBH-P-100, a TG test was performed. The test results are as follows: Figure 6 As shown, under the condition of heating from room temperature to 180℃, the mass fraction of MBH-P-100 decreased by 42.65 wt.%. The test results indicate that MBH-P-100 lost 3.5 C5H5N molecules, meaning that the number of pyridine ligands in MBH-P-100 was 6.

[0055] To demonstrate the effect of drying temperature on the composition of MBH-P-100, a mass weighing test was conducted. The specific test method was as follows: first, a mass weighing test was performed and the data recorded before drying; then, a mass weighing test was performed and the data recorded after drying; finally, the mass difference was calculated based on the mass weighing test results and compared with the theoretical results. The test results are shown in Table 2. Under the condition of a drying temperature of 100℃, the mass of MBH-P-100 decreased by 0.96 wt.%, which is negligible. The test results indicate that during the drying process, MBH-P-100 did not lose C5H5N molecules, meaning that the chemical composition of MBH-P-100 remained Mg(C5H5N)6B. 12 H 12 .

[0056] Table 2 shows the weighing test results for MBH-P-100, MBH-P-150, and MBH-P-170.

[0057] Mass before drying (mg) Mass after drying (mg) Mass fraction reduction change (wt. %) MBH-P-100 500 480 0.96 MBH-P-150 500 301.3 39.7 MBH-P-170 500 286.5 42.7

[0058] To demonstrate the conductivity performance of MBH-P-100, AC impedance testing was conducted. The test results are shown in Table 3 and... Figure 7 As shown,

[0059] At an operating temperature of 90℃, the conductivity of MBH-P-100 is 5.3 × 10⁻⁶. -6 S cm -1 ;

[0060] At an operating temperature of 140℃, the conductivity of MBH-P-100 is 2.3 × 10⁻⁶. -4 S cm -1 As can be seen from the MBH-W obtained in step 1, the addition of pyridine ligands can significantly improve the conductivity by three orders of magnitude.

[0061] Table 3 shows the temperature-conductivity values ​​for MPH-P-100.

[0062]

[0063] To further demonstrate the ionic conductivity of MBH-P-100, i.e., excluding its electronic conductivity, an electron transport number test was conducted. The specific method for the electron transport number test was as follows: First, using the electrolyte sheet under test as the solid electrolyte, a Mo|MBH-P-100|Mo battery was assembled, abbreviated as MBH-P-100. Then, the test was conducted under conditions of a polarization voltage of 1V, a test time of 4000s, and a test temperature range of 120℃. The test results are as follows. Figure 8 As shown, the steady-state current of MBH-P-100 is only in the milliampere range, corresponding to an electronic conductivity as low as 10. -8 S cm -1 Test results show that MBH-P-100 has excellent ion conductivity.

[0064] To demonstrate the electrode compatibility of MBH-P-100, a magnesium symmetric cell test was conducted. The specific test method was as follows: First, using the electrolyte sheet under test as the solid electrolyte and the magnesium sheet as the symmetric electrode, a magnesium symmetric cell was assembled. The resulting magnesium symmetric cell is also simply referred to as MBH-P-100. A constant current density of 0.025 mA cm⁻¹ was then applied. -2 The test was conducted at a temperature of 120℃. The test results are as follows. Figure 9 As shown, the MBH-P-100 has an operating time of 900 minutes and a polarization voltage of less than 2.25V.

[0065] To further demonstrate the effect of drying temperature on performance, Comparative Example 1 and Comparative Example 2 are provided, with solid magnesium ion electrolytes prepared at drying temperatures of 150℃ and 170℃, respectively.

[0066] Comparative Example 1

[0067] A method for preparing a solid magnesium ion electrolyte with a drying temperature of 150°C. The steps not specifically described in the details are the same as the preparation method in Example 1. The difference is that in step 2, the drying temperature is 150°C, and the resulting solid magnesium ion electrolyte is referred to as MBH-P-150.

[0068] To demonstrate the effect of drying temperature on the composition of MBH-P-150, a mass weighing test was conducted. The test results are shown in Table 1. Under a drying temperature of 150℃, the mass of MBH-P-150 decreased by 39.7 wt.%. The test results indicate that MBH-P-150 lost 3 C5H5N molecules, meaning that the chemical composition of MBH-P-150 is Mg(C5H5N)3B. 12 H 12 Compared with Example 1, it can be seen that increasing the drying temperature leads to a reduction in pyridine ligands in the solid magnesium ion electrolyte, that is, the drying temperature directly affects the chemical composition of the solid magnesium ion electrolyte.

[0069] To demonstrate the electrode compatibility of MBH-P-150, a magnesium symmetric cell test was conducted, and the resulting magnesium symmetric cell is referred to as MBH-P-150. The test results are as follows: Figure 10 As shown, the MBH-P-150 achieved a working time of 800 minutes, with the polarization voltage increasing by more than 4V. Compared with Example 1, it can be seen that increasing the drying temperature directly leads to a reduction in ligands, ultimately resulting in a decrease in working time, and a significant increase in polarization voltage, with an increase of 77.8%.

[0070] Comparative Example 2

[0071] A method for preparing a solid magnesium ion electrolyte with a drying temperature of 170°C. The steps not specifically described in the details are the same as the preparation method in Example 1. The difference is that in step 2, the drying temperature is 170°C, and the resulting solid magnesium ion electrolyte is referred to as MBH-P-170.

[0072] To demonstrate the effect of drying temperature on the composition of MBH-P-170, a mass weighing test was conducted. The test results are shown in Table 1. Under the condition of drying temperature of 170℃, the mass of MBH-P-170 decreased by 42 wt.%. The test results indicate that MBH-P-170 lost 3+x C5H5N molecules, meaning that the chemical composition of MBH-P-170 is Mg(C5H5N). 3-x B 12 H 12 Compared with Example 1, it can be seen that increasing the drying temperature leads to a further reduction in pyridine ligands in the solid magnesium ion electrolyte, that is, the drying temperature directly affects the chemical composition of the solid magnesium ion electrolyte.

[0073] To demonstrate the conductivity performance of MBH-P-170, AC impedance testing was performed on it. The test results are shown in Table 4 and... Figure 11 As shown, at an operating temperature of 140℃, the conductivity of MBH-P-170 is 9.3 × 10⁻⁶.-5 S cm -1 Test results show that reducing the amount of pyridine ligands decreases conductivity by two orders of magnitude.

[0074] Table 4 shows the temperature-conductivity values ​​for MPH-P-170.

[0075]

[0076] To demonstrate the impact of other alkali metal coordination hydride materials on performance, Comparative Example 3 is provided, based on Li₂B. 12 H 12 The prepared solid magnesium ion electrolyte.

[0077] Comparative Example 3

[0078] A Na2B-based 12 H 12 The preparation method of the solid magnesium ion electrolyte is the same as that in Example 1, except that in step 1, Li₂B₂ is used. 12 H 12 Replace with Na2B 12 H 12 Preparation of precursor Mg(H2O)3B 12 H 12 The final obtained Mg(C5H5N)6B 12 H 12 The solid magnesium ion electrolyte is named Mg(C5H5N)6B 12 H 12 -Na, abbreviated as MBH-P-Na.

[0079] To demonstrate the conductivity performance of MBH-P-Na, AC impedance testing was conducted. The test results are shown in Table 5 and... Figure 12 As shown, at an operating temperature of 90℃, the conductivity of MBH-P-Na is 2.3 × 10⁻⁶. -6 S cm -1 The test results show that...

[0080] Table 5 shows the temperature-conductivity values ​​of MBH-P-Na.

[0081]

[0082] Although the conductivity of MBH-P-Na is on the same order of magnitude as that of MBH-P-100 at operating temperatures of 30℃ and 140℃, the conductivity of MBH-P-Na is significantly lower than that of MBH-P-100 in the temperature range of 50 to 110℃. Furthermore, at an operating temperature of 90℃, the conductivity of MBH-P-Na is reduced by 0.5 orders of magnitude compared to MBH-P-100.

[0083] Based on the conductivity test results of Example 1 and Comparative Example 3, the following conclusions can be drawn from the variation law of the conductivity of MBH-P-Na:

[0084] When those skilled in the art attempt to compare Li2B at room temperature... 12 H 12 The sum is Na2B 12 H 12 Preparation of Mg(H2O)3B 12 H 12 Precursor, and then Mg(C5H5N)6B is prepared. 12 H 12 When using solid magnesium ion electrolytes, only Li₂B can be obtained. 12 H 12 The sum is Na2B 12 H 12 The conclusion is that it has no substantial impact.

[0085] Therefore, it is impossible to make a scientific, reasonable, and accurate prediction that the conductivity of MBH-P-100 is significantly higher than that of MBH-P-Na under the condition of operating temperature of 90℃.

Claims

1. A solid magnesium ion electrolyte based on pyridine ligands, characterized in that: From Mg(C5H5N) x 2+ Complex cations and [B] 12 H 12 ] 2- Compounds composed of anions, wherein 1 ≤ x ≤ 6.

2. The solid magnesium ion electrolyte based on pyridine ligands according to claim 1, characterized in that: The number of pyridine ligands is 6.

3. A method for preparing a solid magnesium ion electrolyte based on pyridine ligands, characterized in that... Includes the following steps: Step 1, Mg(H2O)3B 12 H 12 The preparation of the precursor first involves Li2B 12 H 12 Dissolved in deionized water, solution A is obtained. Then, under certain conditions, a strong acid ion exchange resin is added to solution A and magnetically stirred to obtain solution B. Excess MgCO3 is added to solution B to react and obtain the precursor solution. Finally, the precursor solution is washed, filtered, and dried to obtain the precursor Mg(H2O)3B. 12 H 12 Abbreviated as MHB-W; Step 2, Mg(C5H5N)6B 12 H 12 To prepare the solution, firstly, under argon atmosphere, the MBH-W obtained in step 1 is placed in a pyridine solution and heated and stirred under certain conditions to obtain a homogeneous mixed liquid. Then, the mixed liquid is vacuum dried to obtain the solid magnesium ion electrolyte Mg(C5H5N)6B based on pyridine ligands. 12 H 12 It is abbreviated as MBH-P.

4. The preparation method according to claim 3, characterized in that: In step 1, Li2B 12 H 12 The mass ratio of hydride to MgCO3 is 3:

1.

5. The preparation method according to claim 3, characterized in that: In step 1, the conditions for stirring solution B are: stirring temperature of 20-40℃ and stirring time of 8-12h. In step 1, the precursor solution is dried by rotary evaporation of the filtrate obtained from filtration to obtain Mg(H2O)6B. 12 H 12 Mg(H2O)6B crystals were then dried at 150℃ for 12-18 hours. 12 H 12 The .6H2O crystals were vacuum dried.

6. The preparation method according to claim 3, characterized in that: In step 2, the mass ratio of MBH-W to pyridine solution is 1:

100.

7. The preparation method according to claim 3, characterized in that: In step 2, the heating and stirring conditions are as follows: heating temperature is 30-50℃, and stirring time is 20-30h. In step 2, the vacuum drying conditions are: drying temperature of 100℃ and drying time of 3-8 hours.

8. The solid magnesium ion electrolyte based on pyridine ligands according to claim 1, characterized in that: When used as a magnesium ion solid electrolyte, MBH-P-100 exhibits a conductivity of 10⁻⁶ at an operating temperature of 140°C. -4 S cm -1 .

9. The solid magnesium ion electrolyte based on pyridine ligands according to claim 1, characterized in that: When used as a magnesium ion solid electrolyte, under the conditions of a polarization voltage of 1V, a test time of 4000s, and a test temperature range of 120℃, the electronic conductivity is 10. -8 S cm -1 .